Elatostema rigidiusculum (Urticaceae), a new species endemic to Sri Lanka - Rajapaksha, Ranil; Gunawardena, Nadeeka; Garasin, Upul; Pushpakumara, Gamini; Premakantha, Tilak; Wijesundara, Siril; Averyanov, Leonid (Phytotaxa, 2019)
Elatostema monandrum var. rigidiusculum, confined to the Bambarabotuwa Forest Reserve in Sabaragamuwa province of Sri Lanka, is reclassified to the rank of species as E. rigidiusculum. We compare it to the morphologically most similar, E. monandrum. The main diagnostic features of E. rigidiusculum are obovate leaves 0.3–1.5 cm long whose laminae are apically crenate, and the presence of sessile receptaculate involucrate inflorescences in both sexes. The proposed IUCN conservation status of E. rigidiusculum is Critically Endangered (CR).